Determination of sodium nitrite content in two meat products by ion chromatography in the western region of Costa Rica - Rojas-Alvarado, Priscilla (2023)
Sodium nitrite is an effective preservative used in meat products for its ability to inhibit pathogenic microorganisms. However, when the quantity of sodium nitrite is high, it can lead to the formation of nitrosamines, compounds with alarming health risks. Existing regulations do not specify a minimum value for sodium nitrite; nevertheless, for sodium nitrite to effectively inhibit the proliferation of pathogenic microorganisms in meat products, it must be present in a minimum quantity of 50 ppm. In this current study, sodium nitrite was quantified using ion chromatography in samples of sausages and “chicharrón” from the western region of Costa Rica, following the methodology validated by Rojas and Vindas (2023). Among the sausage samples analyzed, four out of the total exceeded 125 ppm, while 50.8 % of the samples obtained quantities lower than 50 ppm, indicating insufficient sodium nitrite content in these, which could facilitate the growth of pathogenic microorganisms. In the case of “chicharrón” samples, quantifiable and detectable amounts of sodium nitrite were found, indicating that this product is being adulterated with sodium nitrite, as its addition is not permitted for this product.